2015
DOI: 10.1016/j.imr.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating antimicrobial efficacy of propolis through niosomal-based system for administration

Abstract: BackgroundPropolis is a multicomponent active, complex resinous substance collected by honeybees (Apis mellifera) from a variety of plant sources. This study was designed to improve the antimicrobial efficacy of propolis by engineering a niosomal-based system for topical application.MethodsPropolis was extracted in ethanol and screened for total polyphenol content. Propolis-loaded niosomes (PLNs) were prepared with varying concentrations of Span 60 and cholesterol. The PLNs were evaluated for physicochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 35 publications
2
24
1
Order By: Relevance
“…Values of zeta potential above 30 mV (positive or negative) are adequately high for electrostatic stability and a stable dispersion (Mahajan et al 2012). Patel et al (2015) reported that the zeta potentials of propolis-loaded and free niosomes were -33.2 mV and -38.8 mV, respectively. As shown in Figure 1, niosomes are seen in different shapes and sizes after maturation.…”
Section: Characterization Of Ole Loaded Niosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of zeta potential above 30 mV (positive or negative) are adequately high for electrostatic stability and a stable dispersion (Mahajan et al 2012). Patel et al (2015) reported that the zeta potentials of propolis-loaded and free niosomes were -33.2 mV and -38.8 mV, respectively. As shown in Figure 1, niosomes are seen in different shapes and sizes after maturation.…”
Section: Characterization Of Ole Loaded Niosomesmentioning
confidence: 99%
“…In another study, MIC values of the free and niosomal moxifloxacin were found the same at 0.87 μg/mL against S.aureus, although MIC values of the free moxifloxacin and loaded niosome were found at 6.25 μg/mL and 3.125 μg/mL respectively against P. aeruginosa (Sohrabiet et al 2016). Patel et al (2015) prepared propolis-loaded niosomes and has reported that MIC values of propolis loaded noisome and ethanolic propolis solution against S. aureus was 0.3 mg/mL and 0.5 g/mL, respectively. The MIC values of free vancomycin and vancomycin-loaded niosome against MRSA were reported as 8 μg/mL and 1 μg/mL, respectively (Barakat et al 2014).…”
Section: In Vitro Antibacterial Activity Of Free Ole and Ole Loaded Nmentioning
confidence: 99%
“…Its antimicrobial effect was enhanced when it was incorporated into niosomes that were prepared with varying concentrations of Span 60 and cholesterol. This is because niosomes are able to interact with the bacterial cell envelope, thereby facilitating the diffusion of constituents of propolis across the cell wall [110].…”
Section: Bacterial or Fungal Infectionsmentioning
confidence: 99%
“…GA is also a well-known phytoconstituent of propolis. It shows good antibacterial activity against both Gram-positive and -negative bacteria [18][19][20]. The identification and quantification of GA in various extracts, biological samples and formulations was addressed in some reports.…”
Section: Introductionmentioning
confidence: 99%